Globally distributed teams in the tech industry - Lisa Engel (2021)
The present study makes the leadership of globally distributed teams in the technology industry the subject of discussion. Aiming at detecting crucial leadership aspects in a remote set-up and necessary character traits to accompany this global role, this thesis investigates the differences between dispersed and co-located leadership and the everyday challenges arising through the dispersion. As this is a qualitative study, it is supported by experienced professionals who contributed by participating in interviews concerning the underlying issues. The consulted experts either work for companies from the tech industry or function as trainers for remote teams from various industries. From the experts’ experiences, five major issues for the daily business could be detected: building a remote environment, creating team commitment online, communicating virtually as well as providing feedback and managing conflict remotely. The analysis of the interviews and current studies shows that the desired leadership competencies barely change through the dispersion besides their intensity has to be increased and every task needs to be executed more thoroughly. There is a shift from the classical leadership approaches towards a situational approach is recognizable. Increasing regularity on communication and alignment as well as granting time for socializing can enhance the whole team performance, prevent conflict situations and foster leadership success.
Keywords: virtual teams; leadership; global teams; digitalization; globalization; leadership development